Julkishallinto sosiaalisten käytäntöjen kimppuna: teoreettis-metodologisia näkökulmia julkishallinnon toiminnan tutkimiseen. - Bäcklund, Pia; Kuusisto-Arponen, Anna-Kaisa; Luukkonen, Juho (2017)
In this article, we apply a practice theoretical approach for studying public administration. We argue that social practices are constitutive elements of public administration. This is why it is important to recognize which social practices regulate public administration. We portray two analytical concepts, 'pathologies of action' and 'bolted actualities', which are helpful in studying how particular practices condition public policymaking. The first concept points at subconscious conflictual action at the level of an organization, and the second to an individual's experience of impracticality of action that the actor feels one cannot alter. We utilise institutional ethnography as a methodological framework for studying these social practices.
Hallinnon tutkimus
jufo:2